The Impact of Climate Change on Human Resource Management: A Systematic Literature Review - Setiadi, Muhammad Teguh (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Climate change has become an urgent global issue with far-reaching impacts on the environment and society. In the world of work, climate change affects employee health, well-being and organizational operations. The importance of understanding these impacts and developing effective adaptation strategies is crucial for organizational sustainability. This research aims to identify current research trends regarding the impact of climate change on human resource management (HR), evaluate existing knowledge gaps, and assess practical implications for HR practitioners. This research uses a systematic literature review approach to collect and analyze relevant literature. The databases used include Scopus, Web of Science, and Google Scholar. Key findings include the identification of dominant themes such as the impact of climate change on employees' physical and mental health, various organizational adaptation strategies, as well as the need for green skills development. The developed conceptual framework highlights the relationship between HR policies, employee well-being, green skills development and organizational adaptation strategies. This research makes a significant contribution to the literature by offering an in-depth understanding of the relationship between climate change and HR management. These findings reinforce the urgency of integrating climate change adaptation policies in HR management and provide practical guidance that can be implemented by organizations to increase their resilience and sustainability amidst growing environmental challenges.